Altered Insulin Receptor Substrate 1 Phosphorylation in Blood Neuron-Derived Extracellular Vesicles From Patients With Parkinson’s Disease - Chou, Szu-Yi; Chan, Lung; Chung, Chen-Chih; Chiu, Jing-Yuan; Hsieh, Yi-Chen; Hong, Chien-Tai (Frontiers in Cell and Developmental Biology, 2020)
Introduction: Diabetes increases the risk of Parkinson's disease (PD). The phosphorylation of type 1 insulin receptor substrate (IRS-1) determines the function of the insulin signaling pathway. Extracellular vesicles (EVs) are emerging as biomarkers of human diseases. The present study investigated whether PD patients exert altered phosphorylation IRS-1 (p-IRS-1) inside the blood neuron-derived extracellular vesicles (NDEVs). Research design and methods: 94 patients with PD and 63 healthy controls were recruited, and their clinical manifestations were evaluated. Blood NDEVs were isolated using the immunoprecipitation method, and Western blot analysis was conducted to assess total IRS-1, p-IRS-1, and downstream substrates level in blood NDEVs. Statistical analysis was performed using SPSS 19.0, and p < 0.05 was considered significant. Results: The isolated blood extracellular vesicles were validated according to the presence of CD63 and HSP70, nanoparticle tracking analysis, and transmission electron microscopy. NDEVs were enriched with neuronal markers. PD patients exerted a significantly higher level of p-IRS-1S312 in blood NDEVs than controls. The p-IRS-1S312 levels in blood NDEVs were positively associated with the severity of tremor in PD patients after adjusting age, sex, hemoglobin A1c, and body mass index. Conclusion: PD patients exerted altered p-IRS-1S312 in the blood NDEVs, and also correlated with the severity of the tremor. These findings suggested the association between dysfunctional insulin signaling pathway with PD. The altered p-IRS-1 S312 in blood NDEVs required further cohort study to assess the association with PD progression.